UN Food Systems Summit 2021 - What role science and innovation in the summit and in countries' plans and why? - Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2023)
The UN Food Systems Summit 2021 was different from all six previous food summits held in the past eight decades. New features of this Summit included the fact that it was anchored in the Sustainable Development Goals, focused on food systems, was based on multi-stakeholder engagement, had a focus on country level strategies (so called National Pathways), and the Summit was held in New York rather than Rome, where the UN food agencies are based. Moreover, for the first time the UN called upon science to provide guidance for a food summit. In this article outcomes and political economy processes of the Summit are briefly reviewed, and then a focus is on the role of science for shaping outcomes is quantitatively assessed by reviewing the 118 country reports of National Pathways. In 62% of the countries' strategies science, research, technology and innovation are more or less significantly mentioned. Quality of governance effectiveness is identified as a strong driver of more attention to science in countries' strategies. The relative weight of agriculture in the national economy shows some positive correlation with attention to science too, whereas level of undernutrition does not correlate with attention to science in the strategies. Implications of these findings are drawn for the science - policy interface in food systems, and for the follow-up process to the Summit that has been put in place by the UN until 2030.
Keywords: Q18; F55; Q01; 330; economic development; food system; agriculture; governance; United Nations; science; innovation; technology